Hubungan Lama Membaca dan Menggunakan Komputer Dengan Ametropia pada Mahasiswa Kedokteran Universitas Hang Tuah Semester VII Tahun Ajaran 2016-2017 - Kevin Kalent Angriyanto (Universitas Hang Tuah, 2017)
Background: Ametropia is a refraction error condition which can cause blindness. Environmental factors such as near work activities including using computer and reading are risk factors that play an important role in causing ametropia. This study aimed to determine the correlation between near work activities and ametropia in the seventh semester students of medical faculty Hang Tuah University. Method: This study was an analytic observational study with quantitative method. The sample used in this study were the seventh semester students of medical faculty Hang Tuah University, in total 70 samples.The activity of reading and using computer were obtained by questionnaires, while the refraction profile of students were obtained using Snellen chart and eyeglass card. Result: Of the 70 samples, 38 samples (54,3%) were females and 32 samples (45,7%) were males. The study obtained 43 samples (61,4%) with ametropia condition while 27 samples (38,6%) were normal. Data were analyzed using Spearman correlation, showed there was significant correlation between computer and reading activities and ametropia with p<0,05 (p<α) with positive correlation. Conclusion: There was a significant correlation between reading time and using computer and ametropia among students of medical faculty Hang Tuah University seventh semester.